Etiology and clinico-hematological profile of neonates with pathological unconjugated hyperbilirubinemia: a tertiary care centre experience - Mukhopadhyay, Sujaya; Hassan, Najia (International Journal of Contemporary Pediatrics, 2019)
Background: Jaundice is visible manifestation of raised serum bilirubin. Jaundice in newborns is not an uncommon occurrence. Usually jaundice in newborn is due to elevation of unconjugated bilirubin. There are varied causes of unconjugated hyper bilirubenemia. This study was conceptualized to see the etiology and clinico-hematological profile of neonates with pathological unconjugated hyperbilirubinemia who were admitted in the specific time frame in Sharda Hospital, Greater Noida which is a tertiary care hospital in Western U.P. Methods: This is a retrospective study in which data of all neonates admitted to NICU with unconjugated hyperbilirubinemia requiring phototherapy and/or exchange transfusion in the period 1.7.2018 to 31.12.2018 was collected and analyzed. History including birth weight, mode of delivery, gestational age, mother’s blood group, etc. was recorded. Complete physical examination and investigation done for diagnosis noted. Results: It was seen that out of 438 admissions in NICU, 63% had neonatal jaundice and 18.8% of this had pathological unconjugated hyper bilirubenemia. 63.5% were males and 36.5% females. Majority were term babies. Most of the babies developed jaundice on day 3 of life. In 61% cases no cause for jaundice could be ascertained despite investigations for the same. ABO and Rh incompatibility accounted for 15.30% and 5.7% cases respectively. All patients received phototherapy and 3.8% underwent exchange transfusion. Conclusions: From the study it can be concluded that although blood group incompatibility is an important cause of pathological unconjugated hyper bilirubenemia but in most of the cases no cause is usually found.